Comparing the effects of instructional and transformational leadership on student achievement: Implications for practice. (July 2014) - Shatzer, Ryan H; Caldarella, Paul; Hallam, Pamela R; Brown, Bruce L
The purpose of this study was to compare transformational and instructional leadership theories, examine the unique impact that school leaders have on student achievement, and determine which specific leadership practices are associated with increased student achievement. The sample for this study consisted of 590 teachers in 37 elementary schools in the Intermountain West of the United States. Teachers rated their principals' leadership style according to the Multifactor Leadership Questionnaire (Transformational Leadership) and the Principal Instructional Management Rating Scale (Instructional leadership). Student achievement was measured by a criterion referenced test. Hypotheses were tested using regression analysis. Results indicated that instructional leadership explained more of the variance in student achievement than did transformational leadership. Principals' leadership style tended to have a meaningful impact on student achievement beyond the impact of school context and principal demographics. Specific leadership functions associated with student achievement were also identified and reported. Conclusion, implications and limitations are also discussed.